Face Mapping in Open Pit Mines—A New Approach - Agni Patra; Konstantinos Pilalidis; Francis Pavloudakis; Ioannis Kapageridis (Materials Proceedings, 2023)
In the South Field Mine located in the Lignite Center of Western Macedonia, Northern Greece, a method of photogrammetry was successfully used for mapping quickly and precisely the faces of all mine benches. The important information, which was not available with the conventional way of face sampling, is knowledge of the exact position and thickness of the minable lignite seams. This allows the development of a powerful lignite deposit exploitation tool and can certainly be applied to any other surface mine. Another major advantage of using this methodology concerns the spatial accuracy of the lignite-quality data produced from the lab analysis of the face samples. This information is crucial and may be used as inputs in a database that can be integrated into drilling, survey, and other data, and improve the geological and reserve models of the exploitation area.